Critical communities and aesthetic practices dialogues with Tony O'Connor on society, art, and friendship - Halsall, Francis; Jansen, Julia 1972-; Murphy, Sinead (Contributions to phenomenology, 2012)
This publication brings together eminent philosophers to discuss the inter-dependence of critical communities and aesthetic practices. The contributions share a hermeneutical commitment to dialogue as both a model for critique and as a generator of community.